Meta Analysis of Mathematical Learning Participants According to Piaget Theory - Addiestya Rosa Hutasuhut; Dian Armanto (Peneliti.net, 2022)
The purpose of the study was to analyze 11 studies related to mathematical learning according to the phase of solving the piaget theory, namely: (1) At the sensory stage, it was possible to coordinate the experiences of the senses with movement and gain an understanding of the permanent object (2) pre-operational, the students understood the realityWhile some students are not yet at the stage to use logical thinking or formal operational thinking, many participants have not been able to use concrete operations to form more complex operations. Thus it can be concluded that in the piaget stage, students often cannot face when solving mathematics and learning problems are in concrete operational and formal operational stages. Meanwhile, in the motor and pre-operational stages, students did not experience any obstacles. Therefore, it is hoped that further researchers can pay more attention to the stages of piaget theory in mathematical learning.